Differences level of hybrid resin composite’s hardness based on post-irradiation time with photoactivated light emitting diode - Bianca, Esther; Andang, Milly Armilia; Sukartini, Endang (Universitas Padjadjaran, 2012)
Introduction: Adequate surface hardness of the resin composites is important to obtain optimum clinical performance of the restoratives in stress dental bearing areas. For light-activated resin composites, polymerization begins when curing light initiates polymerization and continues after the curing light goes off. The degree of conversion and hardness of resin composite is also affected by post-irradiation time. The objective of this study was to evaluate the difference of the hardness hybrid resin composite based on post-irradiation time at 10 minutes, 24 hours, and 7 days with photoactivated light-emitting diode (LED) to obtain the optimum hardness. Methods: This study was using a true experimental research method. Thirty samples of hybrid resin composites, disk-shaped of 6 mm in diameter and 2 mm in depth were polymerized by LED LCU at 800mW/cm2 for 20 seconds. The hardness of the resin composite was measured by Vickers Hardness Tester. The result was analyzed statistically with ANOVA. Results: There was a significant difference level of hardness among the three groups. Hardness mean value for post-irradiation time at 10 minutes was 56,4 VHN, for post-irradiation time at 24 hours was 65,8 VHN, and for post-irradiation time at 7 days was 60,0 VHN. Conclusion: There were differences level of hybrid resin composite’s hardness based on the post-irradiation time at 10 minutes, 24 hours, and 7 days with photoactivated LED and the optimum hardness of post-irradiation time at 24 hours.